STRUCTURAL CHARACTERISTICS OF ELECTRODEPOSITED COPPER COATINGS - M. V. Tomić; M. G. Pavlović; Lj. J. Pavlović; N. D. Nikolić (Journal of Engineering & Processing Management, 2009)
The samples of rolled copper were mechanically and electrochemically polished in suitable electrolytes for electrochemical polishing. These substrate surfaces that had been prepared in advance, served as the basis for depositing of copper layers from two baths, namely, from the basic electrolyte(OR) with the following composition: 240 g/dm3 CuSO4 ∙ 5 H2O + 60 g/dm3 H2SO4i as well as from the bath which contained brightening addition agents(OR +DS). STM and AFM techniques show in great detail the structural properties which determine whether the metal surfaceis are as bright as a mirrior or not, that is, whether the obtained topography of the surface is more or less rough. It was determined that a considerable increase of roughness occurred in the samples where copper layers were deposited from the basic sulfate bath (OR) when compared with mechanical, and mechanical-electrochemical samples. In addition, depositing of the samples from the bath with brightening addition agents (OR +DS) resulted in the decrease of surface roughness.
Keywords: Copper; Electrolyte; Coatings